Exergame-based exercise training for depressive symptoms in adults: A systematic review and meta-analysis. (November 2022) - Huang, Kexin; Zhao, Yawei; He, Rendong; Zhong, Tangsheng; Yang, Haiqi; Chen, Yuanxin; Liu, Zixin; Ma, Linya; Jia, Yong; Chen, Li
Abstract: Objective: The aim of this study was to pool existing data to investigate the overall effectiveness of exergame-based exercise training in improving depressive symptoms in adults. Design: A systematic review and meta-analysis. Methods: Ten databases were systematically searched from inception to August 18, 2021, and the search was last updated on November 6, 2021. Standardized mean differences ( SMD s) were calculated using random effects models. The Risk of Bias 2 (RoB 2) tool was used to assess the methodological quality of the studies, and GRADEpro software was used to assess confidence in the cumulative evidence. Funnel plots, Egger's test, and Begg's test were used to analyse publication bias. Sensitivity, subgroup and meta-regression analyses were performed to explore potential sources of heterogeneity. Results: Twenty-one studies were included, and the results showed exergame-based exercise training had a significant effect on depressive symptoms in adults ( SMD  = −0.69; 95% CI, −1.01 to −0.36; P  < 0.001; 19 RCTs, 924 participants; low-quality evidence). The predictive interval was not significant ( 95% PI, −3.45, 2.07). Subgroup analysis showed that in the intervention with the general adult population, game devices with Kinect and long-term interventions appeared to be more effective. Sensitivity analysis found the results to be robust. Conclusion: Exergame-based exercise training has the potential to reduce depressive symptoms. Additionally, different populations, devices and durations of intervention could influence the effect. In the future, high-quality studies with large samples, multiple centres and long follow-up durations should be performed to further explore the efficacy of exergame-based exercise training. Highlights: Exergames had a significant effect on depressive symptoms in adults. Exergames using the Kinect game device seem to have a greater effect. Exergames seem to have a better effect among the general adult population (<65 years). The longer the intervention lasted, the more effective it was.